Obsessive compulsive disorder : a neuropsychological approach - Mukhopadhyay, Pritha; Tarafder, Sreemoyee (Los Angeles, CA : SAGE Publications, Inc., 2018)
This edited book is a comprehensive presentation of Obsessive Compulsive Disorder (OCD) through a neuropsychological framework and the various empirical researches carried out in this domain. The book evaluates whether the information from different research perspectives can form a strong basis for improving the available treatment options for OCD as well as devising newer and better therapy strategies. It thoroughly discusses the various neuropsychological assessment tools that can be used to study the different dimensions of OCD in terms of symptom severity, beliefs, personality and cognition, including executive functions. The book provides guidelines to enhance the skills necessary for developing clinical acumen. The distorted beliefs and functioning, familial factors and scope for inheriting the disorder and obsessive-compulsive spectrum are also described in detail. The book concludes with a discussion of obsessive-compulsive personality traits to help readers arrive at a holistic understanding of OCD, combining neuropsychological and psychoanalytical lenses.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Obsessive-compulsive disorder